스위치드 릴럭턴스 전동기 구동을 위한 히스테리시스 전류 제어형 공진형 C-Dump 컨버터 - 윤용호; 김재문; Yoon, Yong-Ho; Kim, Jae-Moon (전기학회 논문지 P권, 57(2), 2008)
The speed variation of SRM is fulfilled throughout a transition from chopping control to single pulse operation. (i,e., low speed to high speed operation). It is unsatisfied with performance at all operational regimes. In this paper, the operational performance of SRM can be improved by using current hysteresis control method. This method maintains a generally flat current waveform. At the high speed, the current chopping capability is lost due to the development of the back-EMF. Therefore SRM operates in single pulse mode. By using zero-current switching and zero-voltage switching technique, the stress of power switches can be reduce in chopping mode. When the commutation from one phase winding to another phase winding, the current can be zero as fast as possible in this period because several times negative voltage of DC-source voltage produce in phase winding. This paper is compared to performance based on conventional C-dump converter topology and the proposed resonant C-dump converter topology. Simulation and experimental results are presented to verify the effectiveness of the proposed circuit.